Sleep Disorders and Quality of Life in Children with Cerebral Palsy: Sleep and Cerebral Palsy - Bahalkani, Ubedullah; Bharo, Mumtaz Ali; Haque, Tayyaba; Bhanbhro, Bakhtiar Ahmed; Ali, Kamran; Ali, Faiza Kamran (Pakistan Journal of Health Sciences, 2025)
Sleep disorders are common in children with Cerebral Palsy (CP) and can adversely affect their health and quality of life. Objective: To investigate the factors associated with sleep disorders in children diagnosed CP with age ranged from 5 to 10 years. Methods: A cross-sectional study was conducted for six months from March 2024 to August 2024, with 150 children aged 5 to 10 years diagnosed with CP at Department of Pediatrics, Khairpur medical college Khairpur Mir’s. Data on demographics, type of CP, motor function levels (GMFCS), epilepsy presence, physiotherapy intensity, co-sleeping practices, and sleep disorder prevalence were collected. Odds Ratios (OR) and Adjusted Odds Ratios (Adjusted OR) were calculated using chi-square tests and multivariate analysis. Results: Participants were predominantly aged 8 to 10 years (53.3%), with spastic CP being the most common type (56.7%). Significant associations were found between sleep disorders and several factors: type of CP (OR = 2.57, P = 0.004), GMFCS levels III and IV (OR = 2.94, P = 0.001), epilepsy (OR = 2.67, P = 0.01), and low physiotherapy intensity (OR = 3.11, P < 0.001). Multivariate analysis confirmed that the type of CP (Adjusted OR = 2.45, P = 0.007) and motor impairment severity (Adjusted OR = 3.10, P = 0.001) were significant risk factors for sleep disorders. Conclusion: The study highlighted a high prevalence of sleep disorders among children with CP, emphasizing the need for targeted interventions addressing specific risk factors to improve sleep quality and overall well-being.